The Magnitude Of Big Data 5VS In Business Macroclimate - Fam, Soo Fen; Ismail, Noriszura; Shinyie, Wendy Ling (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This paper discusses and features the age of Big Data in business macroclimate. The systematic review of influences the rapid changing business world today. This research explores Big Data and today’s business literature is used in this research to further understand the concepts of Big Data and how Big Data processes, models and the Internet way of utilizing data for breakthrough innovation to acclimate for the age of technology. This paper also examines the depth understanding Big Data and what will Big Data bring to our society and businesses is essential for managers and top management to fully utilize the Big Data for competitive advantage. Big Data 5V are discussed in context of business macroclimate and the Big Data influences towards business processes. The garnered interest of researchers on Big Data in business over the years is evaluated to understand the need to grasp an understanding of 5V and the conceptual framework of big data analytics in business decision making is formed. As a conclusion, the Big Data phenomenon is illustrated in business concepts and intelligence and utilizing Big Data for competitive advantages in the competitive business world with advance information age in this millennium.